Semantics of a Symbolic Component 'Water' in the Modern Greek Phraseological World View - Ирина Витальевна Тресорукова (Philology & Human, 2019)
The article deals with the analysis of food code in Greek phraseology, based on the study of one of its basic symbolic components – water. The food code is one of the components of the cultural code as a whole which forms images and figurative systems, expressed by the combination of linguistic means. Thus, it is regularly reproduced in speech. Phraseological units (PUs) are used as a material for research as they play an important role in cultural linguistics, they create a particular symbolism of the surrounding world. Among other meanings of figurative nomination (e.g. various tropeic meanings, such as metaphors, comparisons, etc.) PUs take on the functions of imaging and expressing the material, spiritual and linguistic view of the world of man and the nation as a whole, while they form various cultural codes as a part of the linguistic view of the world (LVW). As a result of the analysis, it is possible to state that the diversity of understanding the symbolic component water in the Modern Greek PUs is expressed through constructions from all sectors of the LVW. They describe the whole variety of figurative modeling of human life, its events and phenomena, which makes this symbolic component an integral part of the phraseological view of the world of a native Greek speaker.